Optimasi dan validasi metode analisis residu klorpirifos menggunakan High Performance Liquid Chromatography (HPLC) - Abdon Saiya; Dokri Gumolung; Dian Herlinda Octorina Howan (Jurnal Kimia Fullerene, 2017)
One of the most sensitive and selective instrumentation techniques for the analysis of pesticide residues in vegetables at a high level is High Performance Liquid Chromatography (HPLC). To obtain optimum result of measurement, optimization and validation of measurement method is needed. The purpose of this research is to optimize and validate the determination of chlorpyrifos concentration by HPLC method, so it can be used for analysis of chlorpyrifos residues in samples of cabbage vegetables taken from some traditional markets in North Sulawesi. Optimized chromatographic parameters are the composition of mobile phase of water and acetonitrile, mobile phase flow rate, and the volume of the sample injection. While the validated measurement parameters include precision, linearity, detection limits, and quantitation limits. Based on the results obtained using Zorbax Eclipse Plus C18 column, the optimum condition of HPLC was achieved at λmax of 289 nm, mobile phase composition of water : acetonitrile was 10:90, mobile phase flow rate of 0.70 mL/min, and sample injection volume of 15 μL. The result of validation of analytical method shows that analytic performance of determination of chlorpyrifos with HPLC method is very good, it is indicated by measurement parameter such as precision shown with coefficient of variation (CV) was 0,2086%, linearity indicated by correlation coefficient (r) was 0.9963, the detection limit (LOD) of 0.67 ppm, and the quantitative limit (LOQ) of 2.24 ppm, which all meet the requirements. The results of this study indicate that this method can be used for analysis of chlorpyrifos residues in cabbage vegetable samples.